Lymphatic Malformations in Parkes Weber's Syndrome: Retrospective Review of 16 Cases in a Vascular Anomalies Center - Moreno Alfonso, Julio César; Méndez-Maestro, Irune; Coll i Prat, Aniol; Rodríguez-Laguna, Lara; Martínez-Glez, Victor; Triana, Paloma; López-Gutiérrez, Juan Carlos (European Journal of Pediatric Surgery, 2023)
Introduction Parkes Weber's syndrome (PWS) is a rare genetic disorder characterized by overgrowth and vascular malformations, primarily affecting the extremities. While PWS is known to be associated with arteriovenous and capillary malformations, the potential involvement of lymphatic malformations (LMs) has not been previously reported. The objective of this study is to investigate the presence of lymphatic anomalies in PWS patients and their role in the development of limb asymmetry.Materials and Methods This is a retrospective study of patients diagnosed with PWS in a Vascular Anomalies Center from 1994 to 2020. Clinical data were obtained from medical records including diagnostic imaging, lymphoscintigraphy, and genetic testing. The Institutional Review Board and Ethics Committee have approved this study.Results A total of 16 patients aged 18 interquartile range 14.7 years diagnosed with PWS were included (50% female). Six of the 16 patients with PWS had clinical and imaging data suggestive of LM (37.5%) and 3 of them had genetic variants in RASA1 (2/3) or KRAS (1/3). Limb asymmetry was greater in patients with isolated PWS (2.6 ± 0.8 cm) than in the PWS-lymphatic anomalies population (2 ± 0.7 cm), although not significant (p = 0.247). One in 6 patients with PWS-LM required amputation (16.6%) versus 1 in 10 in isolated PWS (10%).Conclusion Lymphatic anomalies may be present in a significant number of patients with PWS and could have a role in limb asymmetry and outcomes. It is paramount to investigate their existence and distinguish them from true overgrowth.
Keywords: Parkes Weber's syndrome; lymphatic malformation; arteriovenous malformation; vascular malformations